Lattice effects on ferromagnetism in perovskite ruthenates - Cheng, J.-G. (National Academy of Sciences, 2013)
Ferromagnetism and its evolution in the orthorhombic perovskite system Sr(1–x)Ca(x)RuO(3) have been widely believed to correlate with structural distortion. The recent development of high-pressure synthesis of the Ba-substituted Sr(1–y)Ba(y)RuO(3) makes it possible to study ferromagnetism over a broader phase diagram, which includes the orthorhombic Imma and the cubic phases. However, the chemical substitutions introduce the A-site disorder effect on T(c), which complicates determination of the relationship between ferromagnetism and structural distortion. By clarifying the site disorder effect on T(c) in several unique series of ruthenates in which the average bond length 〈A–O〉 remains the same but the bond-length variance varies, we are able to demonstrate a parabolic curve of T(c) versus mean bond length 〈A–O〉. A much higher T(c) ∼ 177 K than that found in orthorhombic SrRuO(3) can be obtained from the curve at a bond length 〈A–O〉, which makes the geometric factor t = 〈A–O〉/(√2〈Ru–O〉) ∼ 1. This result reveals not only that the ferromagnetism in the ruthenates is extremely sensitive to the lattice strain, but also that it has an important implication for exploring the structure–property relationship in a broad range of oxides with perovskite or a perovskite-related structure.